Streaming approximation scheme for minimizing total completion time on parallel machines subject to varying processing capacity - Fu, Bin; Huo, Yumei; Zhao, Hairong (Theoretical computer science, 2023)
We study the problem of minimizing total completion time on parallel machines subject to varying processing capacity. In this paper, we develop an approximation scheme for the problem under the data stream model where the input data is massive and cannot fit into memory and thus can only be scanned a few times. Our algorithm can compute an approximate value of the optimal total completion time in one pass and output the schedule with the approximate value in two passes.